“The Effectiveness of International Humanitarian Law in the Israel-Palestine Conflict 2014” - Mohammad Abdullah Bawazir Bawazir (UNIDA GONTOR, 2019)
The international armed conflict between Israel and Palestine in 2014 became a major concern of the international society at the time. The 51-day war left facts and questions about the effectiveness of humanitarian law for international relations students. To measure how effective international humanitarian law is in the conflict, the researcher used the concept of legal effectiveness and the principles in international humanitarian law. The concept states that the law can be said to be effective if the actors can carry out the principles contained therein. In the conflict, it turned out that many violations of the law of war are perpetrated by both parties, especially Israel. It can be seen from some of the principles of international humanitarian law that are ignored; the principle of proportionality, the principle of limitation and the principle of humanity. There is also an increasing number of civilian losses and casualties being an important indication that determines the effectiveness of international humanitarian law.Keywords: The Effectiveness of Law, the Principles of International Humanitarian Law, Casualties, Israel – Palestine